An Exploration of the Involuntary Celibate (Incel) Subculture Online - Liggett O'Malley, Roberta (Journal of interpersonal violence, 2022)
Incels, a portmanteau of the term involuntary celibates, operate in online communities to discuss difficulties in attaining sexual relationships. Past reports have found that multiple elements of the incel culture are misogynistic and favorable towards violence. Further, several violent incidents have been linked to this community, which suggests that incel communities may resemble other ideologically motivated extremist groups. The current study employed an inductive qualitative analysis of over 8,000 posts made in two online incel communities to identify the norms, values, and beliefs of these groups from a subcultural perspective. Analyses found that the incel community was structured around five interrelated normative orders: the sexual market, women as naturally evil, legitimizing masculinity, male oppression, and violence. The implications of this analysis for our understanding of extremism and the role of the internet in radicalization to violence are considered in depth.